Student Perceptions of a Flipped Basic English Practicum Classroom - Ika Sulis Setianingsih; Risa Arroyyani (Universitas Teknokrat Indonesia, 2023)
Flipped classroom, or, in other words, flipped learning setting, has several advantages as well as challenges. In this study setting, flipped classroom was applied to several topics covering grammar lesson prior to the practicum session. This study aimed at investigating the student perceptions of a flipped Basic English Practicum Classroom. Mixed-method research was applied to 44 students, chosen by employing the Simple Random Sampling. A survey was done to gain description on how beneficial the Flipped Classroom model employed in the practicum class, while the interview was also done to give more explanation to the questionnaire data. The data gained were then analyzed in descriptive statistics and coded. The findings showed that flipped classroom employed in this study was not beneficial based on students’ perceptions. Both findings derived from the survey and interview showed that the students preferred a teacher-led lesson for the theory class in preparation for the practicum class, although they also agreed that this model also supports their independent learning. The findings showed that flipped classrooms were found not beneficial, as perceived by the students. As a result, further research should be conducted to find out the reasons why flipped classrooms employed in this setting was not beneficial.Keywords: flipped classrooms, student perception, teacher-led lesson